Techno-economic and carbon emission assessment of a large-scale floating solar pv system for sustainable energy generation in support of malaysia’s renewable energy roadmap - Islam, Md. Imamul; Jadin, Mohd Shawal; Mansur, Ahmed Al; Mohamed Kamari, Nor Azwan; Jamal, Taskin; Hossain Lipu, Molla Shahadat; Mohd Azlan, Mohd Nurulakla; Sarker, Mahidur R.; Shihavuddin, A.S.M. (MDPI, 2023)
Energy generation from renewable sources is a global trend due to the carbon emissions generated by fossil fuels, which cause serious harm to the ecosystem. As per the long-term goals of the ASEAN countries, the Malaysian government established a target of 31% renewable energy generation by 2025 to facilitate ongoing carbon emission reductions. To reach the goal, a large-scale solar auction is one of the most impactful initiatives among the four potential strategies taken by the government. To assist the Malaysian government’s large-scale solar policy as detailed in the national renewable energy roadmap, this article investigated the techno-economic and feasibility aspects of a 10 MW floating solar PV system at UMP Lake. The PVsyst 7.3 software was used to develop and compute energy production and loss estimation. The plant is anticipated to produce 17,960 MWh of energy annually at a levelized cost of energy of USD 0.052/kWh. The facility requires USD 8.94 million in capital costs that would be recovered within a payback period of 9.5 years from the date of operation. The plant is expected to reduce carbon emissions by 11,135.2 tons annually. The proposed facility would ensure optimal usage of UMP Lake and contribute to the Malaysian government’s efforts toward sustainable growth.